Ultrasonic-assisted condensation of chitosan with salicylaldehyde - 段丽红 郭祀远 杨晋青 叶盛权 王兆梅 肖凯军 郑必胜 (Chinese journal of oceanology and limnology, 2009)
In order to synthesize an improved adsorbent for heavy metal ions, we studied the condensation reaction of chitosan with salicylaldehyde in ethanol to form a Schiff base. The effect irradiating the reaction using an ultrasonic liquid processor was contrasted with conventional methods. The IR spectra of condensed chitosan prepared by the two methods showed that their molecular structures were identical. The reaction conditions, including solvents, ultrasonic power density and irradiation time, pH, and reactant ratio, were optimized by orthogonal design. A shorter reaction time and a higher product yield were obtained using ultrasonic-assisted synthesis compared with the traditional method. A condensation degree of 89.63% was achieved using the optimized conditions： i.e. ultrasonic irradiation at 180 W for 60 min; 95% ethanol as the solvent, pH 4.0, and salicylaldehyde：chitosan ratio of 6：1.